Thermal Hydrogen Reduction For Preservation Of Mesoporous Silica Film Nanocomposites With A Hexagonal Structure Containing Amphiphilic Triphenylene - Hendrik O. Lintang; Mohamad Azani Jalani; Leny Yuliati (AIP Publishing, 2024)
Indexed by SCOPUS